Pengaruh Likuiditas, Solvabilitas dan Profitabilitas terhadap Harga Saham dengan Kebijakan Dividen sebagai Variabel Intervening (Studi pada Perusahaan Sub Sektor Restoran, Hotel dan Pariwisata yang Terdaftar di BEI Periode 2020-2022) - Hadu, Charles D. J.; Sonbay, Yolinda Yanti; Manafe, Henny A. (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the significant influence of liquidity on dividend policy, the significant influence of solvency on dividend policy, the significant influence of profitability on dividend policy, the significant influence of liquidity on stock prices, the significant influence of solvency on stock prices, the influence of profitability on stock prices, the influence of dividend policy on share prices, and the ability of dividend policy to mediate the influence of liquidity on share prices, to ascertain whether dividend policy can effectively moderate the impact of profitability on share prices as well as the influence of solvency on share prices listed on the Indonesia Stock Exchange for the 2020–2022 period. This research uses quantitative methodology and associative descriptive research. The findings show that during the 2020-2022 period, dividend policies and share prices in restaurant, hotel and tourism companies listed on the Indonesian Stock Exchange are significantly influenced by liquidity, solvency and profitability. Dividend policy will have a major impact on the share prices of restaurant, hotel and tourism companies listed on the Indonesian Stock Exchange. The impact of liquidity on share prices can be mitigated through dividend policy. Dividend policy is unlikely to mitigate the impact of solvency on share prices. Dividend policy can act as a mediator between the impact of profitability on the share prices of restaurant, hotel and tourism companies listed on the Indonesian Stock Exchange.